Potential Role of Invariant NKT Cells in the Control of Pulmonary Inflammation and CD8+ T Cell Response during Acute Influenza A Virus H3N2 Pneumonia - Christophe Paget; Stoyan Ivanov; Josette Fontaine; Fany Blanc; Muriel Pichavant; Joëlle Renneson; Emilie Bialecki; Julien Pothlichet; Catherine Vendeville; Giovanna Barba–Spaeth; M Huerre; Christelle Faveeuw; et al. (2011)
Abstract Influenza A virus (IAV) infection results in a highly contagious respiratory illness leading to substantial morbidity and occasionally death. In this report, we assessed the in vivo physiological contribution of invariant NKT (iNKT) lymphocytes, a subset of lipid-reactive αβ T lymphocytes, on the host response and viral pathogenesis using a virulent, mouse-adapted, IAV H3N2 strain. Upon infection with a lethal dose of IAV, iNKT cells become activated in the lungs and bronchoalveolar space to become rapidly anergic to further restimulation. Relative to wild-type animals, C57BL/6 mice deficient in iNKT cells (Jα18−/− mice) developed a more severe bronchopneumonia and had an accelerated fatal outcome, a phenomenon reversed by the adoptive transfer of NKT cells prior to infection. The enhanced pathology in Jα18−/− animals was not associated with either reduced or delayed viral clearance in the lungs or with a defective local NK cell response. In marked contrast, Jα18−/− mice displayed a dramatically reduced IAV-specific CD8+ T cell response in the lungs and in lung-draining mediastinal lymph nodes. We further show that this defective CD8+ T cell response correlates with an altered accumulation and maturation of pulmonary CD103+, but not CD11bhigh, dendritic cells in the mediastinal lymph nodes. Taken together, these findings point to a role for iNKT cells in the control of pneumonia as well as in the development of the CD8+ T cell response during the early stage of acute IAV H3N2 infection.